Real Time Monitoring for the Most Vulnerable: Concepts and Methods. (21st March 2013) - Lucas, Henry; Greeley, Martin; Roelen, Keetie
Abstract In assessing the value of different approaches to real‐time monitoring for the most vulnerable, an initial requirement is to set out a conceptual framework that provides at least some degree of clarity as to what precisely is meant by 'real time', 'monitoring' and 'vulnerable'– all terms that can be highly context‐specific. That is the first task addressed here. The second is to consider potential sources of data that might be used to undertake real‐time monitoring and assess their advantages and disadvantages for the present purpose. Four general approaches are considered – community‐based participatory monitoring, sentinel sites, routine data systems and rapid surveys – and selected examples from the literature are given to illustrate the potential use and limitations of their applications.1